Target-Tailored Source-Transformation for Scene Graph Generation - Liao, W.; Lan, Cuiling; Yang, M.; Zeng, Wenjun; Rosenhahn, B. (4th Multimodal Learning and Applications (MULA) Workshop, CVPR 2021, 2021)
.